Administrative Justice Days at New Bulgarian University - Nikolova, Raina (Law Journal of New Bulgarian University, 2023)
The focus of the training practice “Administrative Justice Days at New Bulgarian University” in the autumn semester of the academic year 2022/2023 was directed to events of practical nature accompanying the theoretical training. The occasion was the celebration of the 110th anniversary of the establishment of the Supreme Administrative Court of the Republic of Bulgaria and the 15th anniversary of the establishment of the 28 administrative courts in Bulgaria. The following events took place: 3 public lectures on administrative justice, a discussion on the introduction of mediation in the administrative judicial process, a competition on tax law and tax process, a simulation administrative process, a training on administrative justice in the field of industrial property, a student round table. The invitation of the New Bulgarian University to participate in the event was honoured by prominent representatives of judicial practice and authorities in the field of administrative justice.